A Study on Consumers’ Perception towards Eco-Friendly Products in Kathmandu Valley - Adhikari, Sabina (Nepalese Journal of Economics, 2025)
This study examines a study on consumers’ perception towards eco-friendly products in Kathmandu valley. Consumer perception is selected as the dependent variable. Similarly, product price, product quality, environmental awareness, labeling and packaging are selected as the independent variables. This study is based on primary data with 131 observations. The correlation coefficients and regression models are estimated to test the significance and importance of different factors influencing the consumers’ perception towards eco-friendly products in Kathmandu valley. The study showed that product quality has a positive impact on consumer perception. It means that better product quality better will be the consumer perception. Similarly, product price has a positive impact on consumer perception. It indicates that increase in product price leads to increase in consumer perception. It shows that higher the price better will be the consumer perception. Moreover, environmental awareness has a positive impact on consumer perception. It means that higher the environmental awareness better will be the consumer perception. Likewise, labeling has a positive impact on consumer perception. It shows that better the labeling of the product better will be the consumer perception. Further, packaging has a positive impact on consumer perception. It shows that better the packaging of eco-friendly product better will be the consumer perception.